Ownership Structure, Tax Avoidance and Firm Performance - Ratnawati, Vince; Freddy, Desmond; Hardi, Hardi (Archives of Business Research, 2018)
The aims of this study was to obtain empirical evidence of how ownership structure ie institutional and managerial ownership affect firm performance. The study also examine the moderating role of tax avoidance on the effect of institutional and managerial ownerships on firm performance. A model was developed and tested using sample of 58 manufactured companies from 2012 to 2014, which is listed on Indonesian Stock Exchange. Data were collected and analyzed using least square regression and moderated regression analisys. The result showed that institutional ownership and managerial oenrrship affect firm performance. This study also showed that tax avoidance moderates the effect of both institutional and managerial ownership on firm performance. Keywords: Institutional Ownership, managerial ownership, tax avoidance, firm performance